2022
DOI: 10.3390/ani12223069
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Germ Oil and Propolis Decrease Parasite Burden and Restore Marked Histopathological Changes in Liver and Lung in Mice with Chronic Toxoplasmosis

Abstract: Toxoplasmosis is a parasitic zoonotic disease with a worldwide distribution. Its effects can be critical in immunocompromised patients. However, there is a limited availability of effective, low-toxicity drugs against this disease, particularly in its chronic form. The present study evaluated the effect of propolis and wheat germ oil (WGO) as safe, natural products to reduce Toxoplasma cysts in experimentally infected mice. For the experiment, five groups (10 mice per group) were examined: Group 1: negative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 66 publications
7
3
0
Order By: Relevance
“…In the present work, the results of RT-PCR confirmed the parasitological results since there was a significant reduction in the parasite load in the animals treated with propolis (G3) compared to the positive control group (G2), which had the highest parasite load. The present results are in harmony with previous works that revealed the antiparasitic activity of propolis and WGO in treating chronic toxoplasmosis in mice [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present work, the results of RT-PCR confirmed the parasitological results since there was a significant reduction in the parasite load in the animals treated with propolis (G3) compared to the positive control group (G2), which had the highest parasite load. The present results are in harmony with previous works that revealed the antiparasitic activity of propolis and WGO in treating chronic toxoplasmosis in mice [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…This result could be attributed to the potency of T. gondii tachyzoites for invading and rupturing any nucleated cell; in addition, they strongly stimulate cytokine release, which has a lytic effect on the infected cells [ 68 , 69 ]. The histopathological changes in the liver tissue specimens obtained from the positive control group revealed dilations in the central vein and hepatocellular necrosis, in addition to the presence of bradyzoites between the hepatic tissue and inside the paracentral tissue surrounded by mononuclear cellular infiltration, which is in agreement with some previous works against chronic toxoplasmosis [ 17 , 18 ]. Furthermore, the present study reported the proliferative reaction of Kupffer cells and marked periportal edema around the portal vein.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations